Food, Form, and Visibility: Glub and the Aesthetics of Everyday Life. - BAL, MIEKE (Postcolonial Studies, 2005)
Explores the aesthetics of everyday life in postcolonial cities. Impact of mass migration on cities; Neocultural expression; Cultural phenomena of food; Characteristics of immigrant neighborhood.